Design and development of 3D approach for electromagnetic theory courseware - Ishak, Norshahidatul Hasana; Bakar, Norasiken; Shahdan, Md Lani; Salam, Sazilah; Shahbodin, Faaizah (2011)
This paper will explain about research on development of three dimensional (3D) courseware for EMT subject that have been offers to all Malaysia Technical University Network (MTUN). The EMT courseware was included a multimedia software, three dimensional environment, and exercises for student to be done to test their understanding after using the courseware. This courseware covers up to the whole chapters for EMT subject in multimedia terms but only one chapter that will be using 3D simulation deeply which is coordinate system and transformation. Moreover, this paper explains about the theoretical framework which is divided into three parts which are analysis, design and development, and evaluation. For the second objectives, the instructional design model is used to see the effectiveness of the 3D courseware for teaching and learning starting from defining education media, how to measure the content, authoring program and systematic instructional design and include also the simulation of 3D object. ID model focused on learning and teaching aspects and science education, education process and by using multimedia interactive module. This courseware has six modules which are Note, Tutorial, Simulation, Glossary, Help, and Past Year. Next phase is Development phase, and this phase focus on development of 3D courseware.